In Defense of Platonic Essentialism About Numbers - Wu, Megan (Stance: an international undergraduate philosophy journal, 2021)
In defense of anti-essentialism, pragmatist Richard Rorty holds that we may think of all objects as if they were numbers. I find that Rorty’s metaphysics hinges on two rather weak arguments against the essences of numbers. In contrast, Plato’s metaphysics offers a plausible definition of essentiality by which numbers do have essential properties. Further, I argue that Rorty’s argumentative mistake is mischaracterizing Plato’s definition. I conclude that Plato’s definition of “essential” is a robust one which implies that many properties, beyond those we might intuitively think of, can count as essential properties of objects.